Pelvic organ prolapse after subtotal and total hysterectomy: a long‐term follow‐up of an open randomised controlled multicentre study. Issue 12 (20th August 2013) - Persson, P; Brynhildsen, J; Kjølhede, P; ,
<x xml:space="preserve">Abstract</x> Objective To analyse the development of pelvic organ prolapse (POP) after subtotal (SH) and total hysterectomy (TH) in the long‐term, and to assess patient‐reported symptoms regarding pelvic floor dysfunction (PFD). Design Long‐term follow‐up study of a randomised controlled multicentre study. Setting Seven hospitals and one private clinic in the south‐east of Sweden. Population Of the 184 women who were eligible from the original trial, 151 (82%) responded to a postal questionnaire and 128 (70%) were clinically examined. Methods Postal questionnaire using the short‐form version of the Pelvic Floor Distress Inventory (PFDI‐20) and clinical examination using the POP‐Q system. Multivariate analyses were used. Main outcome measures POP‐Q measurements and symptoms of PFD. Results Follow‐up time was a median of 11.3 years. Less than 3% had stage‐3 prolapse. No significant difference was found in the presence of stage‐2 or higher stage prolapse between the two hysterectomy groups (39% in SH versus 37% in TH; OR 1.28, 95% CI 0.59–2.80). Nor was there any significant difference in the quality‐of‐life measurement between the SH and TH groups [summary score PFDI‐20: median 93 (range 60–201) versus 87 (range 60–186); Fisher's protected least significant difference post hoc test, P = 0.78 ). None of the symptoms of PFD revealed statistically significant differences between the hysterectomy groups. Conclusions This long‐term follow‐up study of PFD showed basically no significant differences in subjective or objective measurements of POP, or in specific pelvic floor quality‐of‐life aspects after SH and TH. However, because of the low statistical power the results are inconclusive. Larger trials, and probably also a longer follow‐up period, are necessary.